DNA repair and inflammatory response genes play a central role in protecting patients with long-standing type 1 diabetes from vascular complications - Özgümüş, Türküler; Sulaieva, Oksana; Begum, Most Champa; Ekström, Ola; Jain, Ruchi; Nilsson, Peter; Sveen, Kari Anne; Berg, Tore Julsrud; Lyssenko, Valeriya (Journal of Diabetes and its Complications, 2025)
Aims: Individuals with type 1 diabetes (T1D) are typically diagnosed at a young age and exposed to lifelong hyperglycaemia. Despite improved metabolic control, the risk of vascular complications remains challenging. However, some individuals remain free from developing major diabetic complications even after long duration, so-called “escapers”. This study investigated transcriptomic biomarkers linked to protection from microvascular complications in the Dialong cohort of long-standing T1D. Methods: Differential gene expression analysis was conducted to identify differences between patients with long-term T1D without complications (non-progressors), those with vascular complications (progressors), and healthy controls without T1D. Results: Among the differentially expressed genes, HERC2, S1PR3, RNASE3, and CD33 were significantly altered between non-progressors and progressors. Functional annotation analyses identified the strongest mechanisms across all groups to be linked to post-translational protein modification, such as Lys-Gly isopeptide bond involved in SUMOylation (p = 5e-17) - a biological process of covalent attachment and detachment of SUMO (Small Ubiquitin-like Modifier) small proteins to modify protein function. The second-ranked pathway was enrichment of DNA repair/damage (p = 6e-5), cell cycle and division (p = 4e-4), and immune response genes (p = 1e-7). Conclusions: These findings underscore the role of post-translational protein modifications, DNA repair pathways and immune tolerance in protecting long-standing T1D patients from vascular complications.
Publisher Copyright: © 2025 Elsevier Inc.
Keywords: Diabetes complications; DNA repair; Inflammation; Transcriptomics; Type 1 diabetes; Vascular protection